2021
DOI: 10.1101/2021.05.26.445903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of straw incorporation and nitrification inhibitor on nitrous oxide emission in various cropland soils and its microbial mechanism

Abstract: Nitrification inhibitor and straw incorporation are widely used to improve crop nitrogen use efficiency in agricultural soil, but their effects on nitrous oxide (N2O) emission across different soil types and the microbial mechanisms remain less understood. In this study, we used controlled experiment and DNA-based molecular analysis to study how nitrification inhibitor (dicyandiamide, DCD) and straw incorporation affect soil nitrogen balance, N2O emission and microbial nitrifiers/denitrifers in three distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/su15032384/s1, Table S1: Publication bias of meta-analysis; Figure S1: Literatures retrieval and screening process; Table S2: List of literature used in the data synthesis. References [72][73][74][75][76][77][78][79][80][81][82][83] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/su15032384/s1, Table S1: Publication bias of meta-analysis; Figure S1: Literatures retrieval and screening process; Table S2: List of literature used in the data synthesis. References [72][73][74][75][76][77][78][79][80][81][82][83] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…A field study found approximately 1.3% of N fertilizer inputs is lost as N 2 O from BF in Northeast China (Liang et al, 2004), which is much greater than the average of 0.6% found for N-fertilized upland soils in China (Xing, 1998). The levels of accumulated N 2 O from BF are higher than those from FF under different fertilization conditions in pot experiments (Zhang et al, 2021). Zhang et al (Zhang et al, 2021) found that nirK and nosZ gene-containing denitrifiers in BF and FF are distinct and that nosZ gene abundance is the only biological factor that significantly determines N 2 O emissions in different soils through a structural equational model.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of accumulated N 2 O from BF are higher than those from FF under different fertilization conditions in pot experiments (Zhang et al, 2021). Zhang et al (Zhang et al, 2021) found that nirK and nosZ gene-containing denitrifiers in BF and FF are distinct and that nosZ gene abundance is the only biological factor that significantly determines N 2 O emissions in different soils through a structural equational model. However, this study did not pay attention to the effects of differences in the composition of denitrifying bacteria in the two soils.…”
Section: Introductionmentioning
confidence: 99%